2018
DOI: 10.1002/mdc3.12631
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine Receptor D3 rs6280 is Associated with Aberrant Decision‐Making in Parkinson's Disease

Abstract: Background The functional Ser9Gly single nucleotide polymorphism (SNP) in the dopamine D3 receptor gene is associated with impulse control disorders (ICD) in Parkinson's disease (PD) in Indian patients. Whether the same SNP modulates impulsivity in PD patients without active ICD is unknown. We aimed to compare decision‐making under uncertainty in PD patients with DRD3 p.S9G (rs6280) variants CT/CC or TT. Methods We conducted a cross‐sectional study including PD patients (n = 78) whose DRD3 p.S9G (rs6280) genot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 22 publications
1
7
0
Order By: Relevance
“…Importantly, our goal was to assess whether variation in genetically mediated DA function predicted flexibility in decision‐making and not to identify SNPs that were predictive of PD incidence or disease severity. In that regard, our sample size is comparable to similar studies examining the contributions of genetic variation to aspects of decision‐making in healthy individuals and in PD (Frank et al, 2007; Frank & Hutchison, 2009; Nikolova et al, 2011; Rajan et al, 2018; Rodriguez‐Jimenez et al, 2006; Williams‐Gray et al, 2008). Second, we conducted a multi‐centre, within‐subject study, and the consistency of our main results across study sites enhances the generalizability of our findings.…”
Section: Discussionsupporting
confidence: 68%
“…Importantly, our goal was to assess whether variation in genetically mediated DA function predicted flexibility in decision‐making and not to identify SNPs that were predictive of PD incidence or disease severity. In that regard, our sample size is comparable to similar studies examining the contributions of genetic variation to aspects of decision‐making in healthy individuals and in PD (Frank et al, 2007; Frank & Hutchison, 2009; Nikolova et al, 2011; Rajan et al, 2018; Rodriguez‐Jimenez et al, 2006; Williams‐Gray et al, 2008). Second, we conducted a multi‐centre, within‐subject study, and the consistency of our main results across study sites enhances the generalizability of our findings.…”
Section: Discussionsupporting
confidence: 68%
“…On the other hand, previous studies showed that the CT genotype in one of the most studied variants associated with ICDs in PD, the Ser9‐to‐Gly substitution at DRD3 (rs6280), was a predictor of ICDs, and it induced a plausible biological effect [33,34]. Also, in a Spanish population, the presence of the C allele induced a higher risk of ICDs in their early‐onset subgroup, but this association was not replicated in the whole cohort [35].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, some studies reported that DRD3 Ser9Gly polymorphism was associated with impulse-control disorders in PD patients, but their results were inconsistent [46]. Rajan et al found that DRD3 Ser9Gly polymorphism is associated with aberrant decision-making under uncertainty in PD patients without active impulse-control disorders [7]. Goetz et al observed that there was a higher frequency of the Gly allele in the hallucinators [8], while Wang et al reported that no significant difference was found between hallucinators and nonhallucinators in the DRD3 Ser9Gly genotypic or allelic distributions [2].…”
Section: Discussionmentioning
confidence: 99%